Genetic Diversity Analysis and Identification of Promising Bell pepper (Capsicum annuum var. grossum Sendt.) Lines under Protected Conditions - Devi, Mayanglambam Bilashini; Pathania, N. K.; Chaudhary, Desraj; Thakur, Nisha (Indian Journal of Hill Farming, 2018)
Genetic diversity analysis of germplasm is useful for the conservation of genetic resources, broadening the genetic basis of cultivars, cultivar protection and its use in future breedingprogrammes. Phenotypic diversity was studied for yield and horticultural traits following multivariate analysis in 29 accessions of bell pepper collected from different regions ofIndia. High genetic diversity was observed amongst the lines and a total of 13 clusters were observed. The inter-cluster D2 value range from 3.54 to 13.60 indicating that the selected accessions were genetically divergent. No intra-cluster distance values (0.00) were observed in most of the clusters except cluster 1 and 2 revealing homogenous nature of the genotypes within the cluster. The genetically more divergent lines were present in cluster 5 and 8 as indicated by maximum inter-cluster distance value (13.60), which offer promise as a breeding stock in hybridization for the isolation of better transgressivesegregants in bell pepper.